2010
DOI: 10.1073/pnas.1011558107
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine modulates synaptic plasticity in dendrites of rat and human dentate granule cells

Abstract: The mechanisms underlying memory formation in the hippocampal network remain a major unanswered aspect of neuroscience. Although high-frequency activity appears essential for plasticity, salience for memory formation is also provided by activity in ventral tegmental area (VTA) dopamine projections. Here, we report that activation of dopamine D1 receptors in dentate granule cells (DGCs) can preferentially increase dendritic excitability to both highfrequency afferent activity and high-frequency trains of backpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
80
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 49 publications
1
80
1
4
Order By: Relevance
“…An in vivo study has shown that the D1R is crucial for maintenance of LTP in CA1 but does not modulate LTP in the dentate gyrus [83] when measured over 4 hours without a specific behavioural context. However, modulatory inputs affecting the dopaminergic system and enhancing LTP in the dentate gyrus have been reported in a context of reward [54,1,42] and reward associated spatial memories [53,37]. These and the present study suggest that previous activity and incoming information during LTP-induction significantly determines different mechanisms involved in LTP-maintenance.…”
Section: Discussioncontrasting
confidence: 44%
“…An in vivo study has shown that the D1R is crucial for maintenance of LTP in CA1 but does not modulate LTP in the dentate gyrus [83] when measured over 4 hours without a specific behavioural context. However, modulatory inputs affecting the dopaminergic system and enhancing LTP in the dentate gyrus have been reported in a context of reward [54,1,42] and reward associated spatial memories [53,37]. These and the present study suggest that previous activity and incoming information during LTP-induction significantly determines different mechanisms involved in LTP-maintenance.…”
Section: Discussioncontrasting
confidence: 44%
“…For example, the activation of D1-family receptors alters excitability in the hippocampus [64,65] and therefore influences the thresholds for the induction of synaptic plasticity or memory encoding. Different hippocampal subregions such as the dentate gyrus, CA1 and subiculum that exert distinct functions in information processing are also modulated by the activation of D1 receptors [37,[66][67][68][69].…”
Section: Discussionmentioning
confidence: 99%
“…These enhanced monoaminergic modulations would greatly increase excitatory drive to CA3 pyramidal cells by the mossy fibers. Furthermore, increased D 1 -like receptor expression in the granule cells may facilitate the induction of long-term potentiation at the perforant path granule cell synapse (Hamilton et al, 2010;Kusuki et al, 1997). Together with changes in intrinsic functional properties of granule cells caused by dematuration, the altered monoaminergic synaptic modulation is likely to have a significant impact on propagation of neuronal signals through the dentate gyrus, thereby possibly contributing to neuronal bases for mechanisms of action of SSRIs.…”
Section: Discussionmentioning
confidence: 99%